2020
DOI: 10.1097/aog.0000000000003932
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Couple’s Human Immunodeficiency Virus Testing and Counseling in the Antenatal Care Setting

Abstract: OBJECTIVE: To describe a pilot implementation of couple’s human immunodeficiency virus (HIV) testing and counseling in an antenatal care clinic in the United States. METHODS: We used a cross-sectional study design. Couples were recruited from an antenatal care clinic of a large, urban, tertiary medical center, and were eligible if both partners agreed to receive HIV test results together and reported no coercion to participate in testing and counseling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Study findings here revealed that the current sample of health care providers overall endorsed CHTC as an HIV testing and care engagement modality. Other studies have found the same, for example in the U.S., formative work has found that both health consumers and health providers, support active couple-based modalities for HIV/STI prevention and care 15,35 as a way for mitigating transmission. Leblanc et al (2019) found that among 22 U.S. health providers endorsed CHTC and thought that it made sense when attempting to mitigate HIV transmission between partners and within communities.…”
Section: Discussionmentioning
confidence: 72%
“…Study findings here revealed that the current sample of health care providers overall endorsed CHTC as an HIV testing and care engagement modality. Other studies have found the same, for example in the U.S., formative work has found that both health consumers and health providers, support active couple-based modalities for HIV/STI prevention and care 15,35 as a way for mitigating transmission. Leblanc et al (2019) found that among 22 U.S. health providers endorsed CHTC and thought that it made sense when attempting to mitigate HIV transmission between partners and within communities.…”
Section: Discussionmentioning
confidence: 72%
“…Secondary analyses of “2GETHER” intervention further revealed the increased motivation to test for HIV with one’s partner for MSM with high internalized stigma. 48 However, given the low coverage of CHTC and multi-level barriers to the implementation but high willingness to use this service among MSM, 22 , 99 , 100 , 101 there remains a need for more research on the development, implementation and promotion of male couple-based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies in the US have assessed attitudes toward or effectiveness of interventions to offer HIV testing to partners of pregnant people. The studies that have been done have demonstrated a desire for partner testing but have also highlighted low uptake of testing and multiple barriers to testing ( 34 , 35 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Couples' HIV testing has been evaluated for its ability to increase condom use within a partnership, and is effective, but studies in the US have primarily been done outside of the context of pregnancy and prenatal care ( 36 ). In one urban academic antenatal care setting in the US, couples who received couples HIV testing and counseling reported a very high level of acceptability and increased ease in having conversations around safe sex ( 37 ). However, only 8% of eligible couples consented for the study.…”
Section: Evidence-based Interventionsmentioning
confidence: 99%